Analisis Faktor-Faktor yang Mempengaruhi Efektivitas Keperawatan Komunitas dalam Meningkatkan Kesehatan Masyarakat di Wilayah Desa Pammulukang, Kecamatan Kalukku, Kabupaten Mamuju, Sulawesi Barat Tahun 2025 - Musdalifah, Musdalifah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Community nursing is a form of health care that focuses on promotive, preventive, curative, and rehabilitative efforts to improve public health. However, the effectiveness of its implementation is often influenced by various factors such as human resources, infrastructure, government support, and community participation. This study aims to analyze the factors influencing the effectiveness of community nursing in Pammulukang Village, Kalukku District, Mamuju Regency, West Sulawesi in 2025. This study used a descriptive analytical design with a cross-sectional approach. The population was the Pammulukang Village community and community nurses involved in health services, with a sample of 120 respondents selected using purposive sampling. The research instrument was a structured questionnaire. Data were analyzed using the chi-square test and logistic regression. The results showed that health worker competence (p=0.002), availability of infrastructure (p=0.010), government support (p=0.016), and community participation (p=0.001) were significantly associated with the effectiveness of community nursing. The dominant factor was community participation with an OR=3.45. This study concludes that community participation is key to the success of community nursing in improving health. It is recommended that village governments and health workers place greater emphasis on community-based empowerment programs.